Den befolkade ensamheten: Författarrollen i Strindbergs Ensam och de intertextuella banden till Baudelaires flanörpoet - Wennborg, Göran (Tidskrift för litteraturvetenskap, 2011)
Populated Solitude: The Role of the Author in Strindberg’s Ensam and the Intertextual Ties to Baudelaire’s Flâneur-Poet In its portrayal of an anonymous writer leading a secluded life in Stockholm, August Strindberg’s novel Ensam (1903) has commonly been perceived as an autobiographical work. This article looks beyond these biographical bonds, and illuminates the novel from an inter-textual perspective, drawing upon the works of Charles Baudelaire. Focusing on the role of the author in Ensam, the article examines how the author’s encounters with the city – its theatrical expressions and its crowds – transforms impressions into literature. In so doing, the figure of the author bears strong resemblance to Baudelaire’s flâneur-poet. The article argues that, in addition to the novel’s biographical background, Ensam can be placed in, and understood through the context of the flâneur literature for which Baudelaire is known.